Phytochemical screening and standardization of ethanol extract of Guava Leaves (Psidium guajava L.) with specific and non-spesific parameters - Sukma Dwyastati Biadi; Varda Arianti; Dimas Adrianto; Devi Maulina (PT WIM Solusi Prima, 2026)
This study aims to conduct phytochemical screening and standardization of guava leaf ethanol extract (Psidium guajava L.) originating from Gunung Putri, Bogor Regency, West Java. The extract was derived by means of maceration procedure utilizing 96% ethanol as the extraction medium, and phytochemical analysis confirmed the presence of flavonoids, alkaloids, tannins, saponins, terpenoid/steroid compounds, as well as glycosides. Quality evaluation based on specific and non-specific parameters showed results that met the standards: drying loss of (<10%), total ash content of (<8,4%), specific gravity of 0.99 g/mL, water content of 5.2% (<10%), and negative heavy metal contamination. These results indicate that guava leaves from the Gunung Putri area have a phytochemical profile and extract quality that are suitable for the development of standardized herbal preparation raw materials. Geographical aspects also contribute to the validity of the results and can be a reference for standardization based on plant growing areas.